Native Advertising: Ads in Disguise as Editorials - Cornwell, Sarah E.L.; Rubin, Victoria L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
Native advertising, paid for by corporate funding, may fool news readers into thinking that they are reading investigative journalism editorials. Such misleading practice constitutes an internal threat to the profession of journalism and may further deteriorate mainstream media trust. If information users are unaware of the Native Ads original promotional nature, they may find themselves insufficiently informed or mislead by its content. This study investigates cases of Native Ads in terms of their contextual use, distinctive features, and likeness to editorials. LIS should aim to provide clear discernment guidelines and consider automated user alerts.